Effects of ubiquinone-10 supplementation and high intensity training on physical performance in humans - Malm, C.; Svensson, M.; Ekblom, B.; Sjöding, B. (Acta Physiologica Scandinavica, 1997)
This study investigated the effects of oral supplementation with ubiquinone-10 (Q10) (n = 9) compared with a placebo (n = 9) on aerobic and anaerobic physical performance over 22 days of supplementation. The supplementation period included 5 days of high intensity anaerobic training between days 11 and 14. The results demonstrated, that on an anaerobic (10 10 s) cycling test, the placebo group showed a significantly greater improvement than the Q10-group after a supplementation and training period (P < 0.001). Further, the Q10 group had a significantly lower increase in total work performed during the seven training sessions (15 10 s) compared with the placebo group (P < 0.001). There was a significant increase in maximal blood lactate accumulation during cycling in the both groups, when compared with levels before the training and recovery period. There was no significant difference between the groups, either in VO2max determined during running, or in submaximal and peak VO2, Rate of Perceived Exertion, respiratory quotient, blood lactate concentration or heart rate determined during submaximal and maximal cycling. Although insignificant(P = 0.10.3), there was evidence of higher submaximal VO2 (5580% of VO2peak) during cycling in the Q10-group compared with the placebo group after training and recovery. It is concluded that with high intensity anaerobic training, there was a significantly greater increase in anaerobic performance in the placebo group compared with the Q10 group. The results suggest less increase in physical performance with Q10 supplement and high intensity anaerobic training, compared with placebo.